2012
DOI: 10.1177/1040638712463692
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Avian coronavirus infectious bronchitis virus type QX infection in Switzerland

Abstract: Infectious bronchitis, a disease of chickens caused by Avian coronavirus infectious bronchitis virus (IBV), leads to severe economic losses for the poultry industry worldwide. Various attempts to control the virus based on vaccination strategies are performed. However, due to the emergence of novel genotypes, an effective control of the virus is hindered. In 1996, a novel viral genotype named IBV-QX was reported for the first time in Qingdao, Shandong province, China. The first appearance of an IBV-QX isolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In contrast, the QX-type IBVs prevalent in China today primarily cause typical nephritis. Since the discovery of QXIBV, LX4, and A2 strains in 1990s, the QX-type has become the predominant IBV genotype in China and spread to Europe [28][29][30] . Previously, the QX-type IBV accounted for 50-60% of field IBV isolates from 2004-2012 [3][4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the QX-type IBVs prevalent in China today primarily cause typical nephritis. Since the discovery of QXIBV, LX4, and A2 strains in 1990s, the QX-type has become the predominant IBV genotype in China and spread to Europe [28][29][30] . Previously, the QX-type IBV accounted for 50-60% of field IBV isolates from 2004-2012 [3][4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…An IBV variant identified in China was the QX variant, a significant IBV type that has been circulating in China for a long period of time. The QX variant was first reported in China in 1998 [28] and spread quickly across Russia [3] and many European countries, including the Netherlands, Germany, France, Belgium, England, and Spain [1,2,24,25]. These strains evolved to form a new subgroup of QX isolates.…”
Section: Infectious Bronchitis Virus (Ibv) Is a Member Of The Genusmentioning
confidence: 99%
“…Province, it was classified to QX genotype, and it was the prevalent genotype in Sichuan province and worldwide. (4,7,30,31) Recombinant analysis of the Sczy3 genome demonstrated that Sczy3 is a chimeric strain derived from QX and H120. (32) Monoclonal antibodies are a powerful tool for virus detection and characterization.…”
mentioning
confidence: 99%